Screen adaptation : a scriptwriting handbook - Portnoy, Kenneth, 1946- (Focal Press, 1998)
Screen Adaptation: A Scriptwriting Handbook, Second Edition examines the challenges screenwriters face when adapting novels, plays, and short stories for the screen. Thoroughly updated to include new exercises and examples from current films, this book provides practical, usable information on how to find the best plot line for a script, choose key characters, and understand the goals and formats of different genres. Both beginning writers and seasoned professionals will find the tools necessary to evaluate a prospective source and create a successful screenplay.